Russo-Japanese War: Strategy, Superiority And Its Impact On The Resurrection Of Indonesian Nationalism (Paramita: Historical Studies Journal, 2021)
The Russo-Japanese War (1904-1905) was an essential milestone in war history in the 20th century, especially in Asia. For the first time in a modern war, Japan, which was positioned as the representative of the colored nation (Asia), succeeded in defeating Russia, which was considered to represent the white nation (Europe) which was identical to the face of imperialism-colonialism. Departing from this reality, this study intends to specifically analyze the history of the Russo- Japanese war and its influence on the rise of Indonesian nationalism. Regarding methodology, this research uses a qualitative approach with critical discourse analysis, which critically-synchronously examines the discourse of the history of the Russo-Japanese War. The collecting data using references and Forum Group Discussion (FGD) by inviting five experts. The results of this study appointment: (1) the spirit of nationalism movement when it is loaded with cosmopolitanism, which is influenced by the global geopolitical constellation; (2) Japan’s victory in the Russo-Japanese War was used by national movement figures to raise nationalism against colonialism; and (3) The strategy and superiority of Japan provided the basis for inspiration on the importance of modernity and the insight of the Indonesian nationality to be equal with European nations. This study implies that in building Indonesian nationalism, Sukarno adopted the spirit of Japanese modernization as part of his strategic culture. On the other hand, Sukarno also gave a critical view of imperialism and the expansionist movement of the Japanese “Lebensraum” in Asia.Perang Rusia-Jepang (1904-1905) merupakan tonggak penting dalam sejarah perang di abad ke-20, terutama di Asia. Untuk pertama kalinya dalam perang modern, Jepang yang diposisikan sebagai wakil bangsa kulit berwarna (Asia), berhasil mengalahkan Rusia yang dianggap mewakili bangsa kulit putih (Eropa) yang identik dengan wajah imperialisme- kolonialisme. Berangkat dari kenyataan tersebut, penelitian ini bermaksud menganalisis secara khusus sejarah perang Rusia-Jepang dan pengaruhnya terhadap kebangkitan nasionalisme Indonesia. Dari segi metodologi, penelitian ini menggunakan pendekatan kualitatif dengan analisis wacana kritis, yang mengkaji secara kritis wacana sejarah Perang Rusia-Jepang. Pengumpulan data menggunakan referensi dan Forum Group Discussion (FGD) dengan mengundang lima pakar. Hasil kajian ini mengangkat: (1) semangat gerakan nasionalisme yang sarat dengan kosmopolitanisme, yang dipengaruhi oleh konstelasi geopolitik global; (2) Kemenangan Jepang dalam Perang Rusia-Jepang dimanfaatkan oleh tokoh-tokoh pergerakan nasional untuk membangkitkan nasionalisme melawan kolonialisme; dan (3) Strategi dan keunggulan Jepang menjadi dasar inspirasi pentingnya modernitas dan wawasan kebangsaan Indonesia sejajar dengan bangsa Eropa. Kajian ini menyiratkan bahwa dalam membangun nasionalisme Indonesia, Sukarno mengadopsi semangat modernisasi Jepang sebagai bagian dari budaya strategisnya. Di sisi lain, Sukarno juga memberikan pandangan kritis terhadap imperialisme dan gerakan ekspansionis “Lebensraum” Jepang di Asia.